POLITICAL CORRUPTION AND 'ONE CHANCE' DEMOCRACY IN NIGERIA - Remi Chukwudi Okeke; Chukwuemeka Vincent Muoneke; Jude Odigbo (Social Sciences and Education Research Review)
The paper studied political corruption and 'one chance' democracy in Nigeria. It is acknowledged in the work that corruption is a universal disorder present in different dimensions in all modern states. The Nigerian trajectory of corruption is denoted as atypically challenging in the analysis, as corruption is even communally tolerable in the country. Under the template of the elite theory, the paper explored how corruption has engendered in Nigeria, the brand of democracy denotable as one chance democracy. Under this practice, voters are functionally robbed of their votes through vote buying, by corrupt and moneyed politicians. The antics of these political elites are in tandem with the operational bravado of the original one chance practitioners, who use their commercial cabs to rob, maim or kill unsuspecting commuters. Corruption and one chance democracy have accordingly left the citizenry bewildered at best, and invariably endangered as members of a purposeful nation. The paper concludes that by and large, the aboriginal one chance operators will close in on their political elite counterparts for an epic confrontation that would cause the return of the Nigerian state to the path of true democratic ethos.